The immediate result of replacing the aortic root with a decellularized valve-containing allograft in a child - A. V. Nokhrin; V. A. Bolsunovsky; E. S. Kulemin; T. L. Kornishina; E. V. Trizna; L. L. Popova; E. M. Gvozd; D. O. Ivanov (Вестник хирургии имени И.И. Грекова)
Cardiac surgery of the aortic valve in pediatric patients is an urgent problem. Performing an open aortic commissurotomy and planar resection of the valves during the newborn period allows to obtain suboptimal results and postpone subsequent interventions indefinitely. With an unsatisfactory result of open aortic commissurotomy in children of the first years of life, the need to search for optimal surgical tactics arises. The presented article describes the technique of replacing the aortic root with a decellularized valve-containing allograft in a child of 14 months of life. A good immediate result of the operation is associated with the ability of the allograft to provide physiological hemodynamics in the aortic position. The advantages of the described technique are the reduction in the time and complexity of surgical intervention, the possibility of preserving own pulmonary valve, the probability of recellularization and the possibility of graft growth with the growth of the child. That is precisely why the presented technique should be considered as an alternative to Ross surgery, especially if there are anatomical contraindications to it.